Doe Productivity of Boerawa Goat on Rural Condition - Adhianto, K; Ngadiyono, N; Budisatria, I Gede Suparta; Kustantinah, Kustantinah (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2013)
Abstract. This research was carried out at Gisting sub-District, Tanggamus Regency, in order to find out doe productivity of Boerawa goat on rural on condition. This research involved 120 doe Boerawa goat housed in elevated barns. Measurements were performed to evaluate the litter size, birth weight, weight at weaning, and pre-weaning mortality. The results of the present research showed that birth weight of the kids was 3.10 kg and 2.94 kg for male and female, respectively. The average birth weight was based on the type of birth 3.20 kg and 3.04 kg for the single versus twin born kids. It was documented that the average weight at weaning of the kids were 17.12 kg and 16.23 kg for male and female, respectively. Whereas based on birth type, the average weight was of the single born kids and the twin at weaning were 17.30 versus 16.63 kg. In addition, doe reproduction index was 2.36 weaned kids/year, and the average doe productivity was 41.52 kg.Â Keywords: Boerawa goat, doe productivity, rural condition.Â Abstrak.Â Penelitian ini dilakukan di Kecamatan Gisting Kabupaten Tanggamus, dalam rangka untuk mengetahui produktivitas induk kambing Boerawa pada kondisi pedesaan. Penelitian ini melibatkan 120 induk kambing Boerawa yang dipelihara di kandang panggung. Pengukuran dilakukan untuk mengevaluasi ukuran jumlah cempe sekelahiran, bobot lahir, bobot sapih, dan kematian pra-sapih. Hasil dari penelitian ini menunjukkan bahwa bobot lahir cempe adalah 3,10 kg dan 2,94 kg (masing-masing untuk jantan dan betina). Bobot lahir rata-rata didasarkan pada tipe kelahiran tunggal dan kembar adalah masing-masing 3.20 kg dan 3,04 kg. Diperoleh hasil bahwa bobot sapih adalah 17,12 kg dan 16,23 kg (masing-masing untuk jantan dan betina). Sedangkan berdasarkan tipe kelahiran, bobot sapih rata-rata dari tipe kelahiran tunggal dan kembar adalah 17.30 dan 16.63 kg. Selain itu, indeks reproduksi induk sebesar 2,36 cempe sapihan/tahun, dan produktivitas induk rata-rata adalah 41,52 kg. Kata kunci: Kambing Boerawa, produktivitas induk , kondisi pedesaan.K Adhianto et al./Animal Production 15(1):31-39, January 2013